2019
DOI: 10.15321/geneltipder.2019150558
|View full text |Cite
|
Sign up to set email alerts
|

Psöriasisde Tamamlayıcı Ve Alternatif Tıp Yöntemleri Kullanımı Ve Beslenmeyle Olan İlişki: Bir Anket Çalışması

Abstract: ÖzAmaç: Bu çalışmayla dermatoloji polikliniğimize başvuran psöriasis hastalarının Tamamlayıcı ve Alternatif Tıp (TAT) yöntemleri hakkındaki bilgi ve yaklaşımları ile psöriasis hastalığının besinlerle olabilecek ilişkisini değerlendirmeyi amaçladık.Gereç ve Yöntem: Çalışmamız Mayıs 2018-Temmuz 2018 tarihleri arasında dermatoloji polikliniğine psöriasis nedeniyle başvuran 111 hasta ile anket çalışması olarak planlandı. Anket soruları hastalarla poliklinik ortamında yüz yüze soru-cevap şeklinde uygulandı.Bulgular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Islamoglu et al found in the study in which they evaluated the status of using TCM methods in patients with psoriasis that there was no correlation between gender and educational background and TCM use, however, the mean age of the ones who used TCM was lower than that of the ones who did not use (12). Akcay et al found in the study in which the use of complementary and alternative treatment in children and parental information were evaluated that there was no correlation between TCM use and the age and educational background of the parent (13).…”
Section: Discussionmentioning
confidence: 99%
“…Islamoglu et al found in the study in which they evaluated the status of using TCM methods in patients with psoriasis that there was no correlation between gender and educational background and TCM use, however, the mean age of the ones who used TCM was lower than that of the ones who did not use (12). Akcay et al found in the study in which the use of complementary and alternative treatment in children and parental information were evaluated that there was no correlation between TCM use and the age and educational background of the parent (13).…”
Section: Discussionmentioning
confidence: 99%